2020
DOI: 10.1039/d0tc03835k
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of quantum dot size in the ultrafast charge carrier dynamics at the perovskite–quantum dot interface

Abstract: Deciphering the electrons and holes (e, h) dynamics at the interfaces of photoexcited hybrid materials at different densities of photoexcited charge carriers is paramount to the development of efficient optoelectronic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…There are no significant differences in terms of structural and optical properties over the concentration of added PbS QDs. However, the presence of FAPI-PbS QDs, which do not affect the emission wavelength and the bandgap value, Figure S6e,f, induced a decrease in the PL emission intensity of perovskite film with respect to reference FAPI (air) film, Figure S6e. …”
mentioning
confidence: 98%
See 1 more Smart Citation
“…There are no significant differences in terms of structural and optical properties over the concentration of added PbS QDs. However, the presence of FAPI-PbS QDs, which do not affect the emission wavelength and the bandgap value, Figure S6e,f, induced a decrease in the PL emission intensity of perovskite film with respect to reference FAPI (air) film, Figure S6e. …”
mentioning
confidence: 98%
“…It is observed that the charge carriers are relatively long-lasting in the reference FAPI (air) films than 1 mg/mL (air) films. In this context it is worth pointing out that the effect of PbS addition in the steady-state PL and TRPL behavior is the result of two concomitant and opposite mechanisms: (i) the increase of FAPI domain size due to the seed effect for crystal growth of PbS QDs additives and (ii) the PbS QDs acting as nonradiative recombination center. , The space charge-limited current (SCLC) is measured to quantitatively evaluate the trap density ( n trap ) in the FAPI (air) and 1 mg/mL (air) perovskite films. Figure S16b, shows the dark current–voltage ( I – V ) curves of electron-only devices with the configuration of ITO/SnO 2 /FAPI (air) or 1 mg/mL (air))/PCBM/Au.…”
mentioning
confidence: 99%
“…Reproduced with permission. [ 126 ] Copyright 2020, The Royal Society of Chemistry. B) Absorption and dual emission of PbS/CsPbI 3 heterostructural QDs.…”
Section: Carrier Dynamics In Quantum Dot/perovskite Systemsmentioning
confidence: 99%
“…PbY–perovskite nanocomposites have been used in photodetectors, , LEDs, , and photovoltaics. , Remarkably, PbS NC inclusions can provide stability to the cubic phase of perovskites suppressing the cubic–orthorhombic phase transition, and perovskite passivation layers enhance charge carrier separation in PbS NCs by providing adequate energy alignment . Furthermore, PbY nanocomposites with secondary phases might be of great importance for thermoelectrics. , …”
mentioning
confidence: 99%
“…42−44 Alternative approaches to dope NC-based solids have focused on changing the NC surface chemistry, 30,36,38,45−48 inducing partial cation exchange, 49,50 and blending with other NCs. 35,51,52 PbY−perovskite nanocomposites have been used in photodetectors, 53,54 LEDs, 55,56 and photovoltaics. 57,58 Remarkably, PbS NC inclusions can provide stability to the cubic phase of perovskites suppressing the cubic−orthorhombic phase transition, 59 and perovskite passivation layers enhance charge carrier separation in PbS NCs by providing adequate energy alignment.…”
mentioning
confidence: 99%